Integration of depositional process modelling, rock physics and seismic forward modelling to constrain depositional parameters - Alkaff, Mohammed Ali O (Curtin University, 2015)
Stratigraphic modelling parameters can be modified by generating synthetic seismic data from the stratigraphic model via integration of the stratigraphic model, rock physics and seismic forward modelling. Rock physics is used to convert geological parameters to elastic parameters. These are then used to generate synthetic seismic data via seismic forward modelling. Synthetic data is then compared with its corresponding observed data and the stratigraphic modelling parameters are modified based on the comparison results.